Novel Functions and Regulation of Cryptic Cellobiose Operons in Escherichia coli - Parisutham, Vinuselvi (Public Library of Science, 2015)

(untitled) (PLoS One)
Presence of cellobiose as a sole carbon source induces mutations in the chb and asc operons of Escherichia coli and allows it to grow on cellobiose. We previously engineered these two operons with synthetic constitutive promoters and achieved efficient cellobiose metabolism through adaptive evolution. In this study, we characterized two mutations observed in the efficient cellobiose metabolizing strain: duplication of RBS of ascB gene, (β-glucosidase of asc operon) and nonsense mutation in yebK, (an uncharacterized transcription factor). Mutations in yebK play a dominant role by modulating the length of lag phase, relative to the growth rate of the strain when transferred from a rich medium to minimal cellobiose medium. Mutations in ascB, on the other hand, are specific for cellobiose and help in enhancing the specific growth rate. Taken together, our results show that ascB of the asc operon is controlled by an internal putative promoter in addition to the native cryptic promoter, and the transcription factor yebK helps to remodel the host physiology for cellobiose metabolism. While previous studies characterized the stress-induced mutations that allowed growth on cellobiose, here, we characterize the adaptation-induced mutations that help in enhancing cellobiose metabolic ability. This study will shed new light on the regulatory changes and factors that are needed for the functional coupling of the host physiology to the activated cryptic cellobiose metabolism.